Propuesta de psicoterapia breve enfocada en la disminución de los síntomas ansioso-depresivos de los pacientes pre-quirúrgicos y sus familiares en el Área de Cirugía del Hospital General Isidro Ayora de la ciudad de Loja. Periodo mayo-junio 2015 - Mora Morales, Ronald Leonardo (2015)
A surgical procedure demands stress, expressed in pathological symptoms in patients and their relatives to surgical procedures. The research aimed to generate a proposal of “Brief Psychotherapy”, focused on reducing anxious-depressive symptoms in pre surgical patients and their relatives, determined the levels of anxiety and depression in pre surgical patients and their relatives; and, make a re test to postsurgical patients and their relatives to determine their levels anxious-depressive without previously there any psychological work in them, for the purpose of create the need for the development of a proposal “Brief Psychotherapy” . The research was descriptive of cross-section with a quantitative and qualitative approach, for it was used a socio demographic survey, scales HAD, HARS and BDI. The population was established in the Area of Surgery HGIAL, and the sample was enclosed in twenty patients and twenty relatives. The results show that pre surgical anxiety occurs in 60% of patients, while 20% showed depression. In the families, preoperative anxiety was 95% and 85% showed depression. After surgery the re test clarified that 75% of patients had anxiety and 25% depression. Generally concludes that anxious depression levels in patients and their relatives in the pre and postsurgical stages validate the creation and implementation of the proposal “Brief Therapy” in favor of creating an integral, objective and real health. Keywords: Brief Psychotherapy, Anxiety and Pre surgical Depression, Integral Health, Mental Health.